Balanced leadership : making the best use of personal and team leadership in projects - Müller, Ralf, 1957-; Drouin, Nathalie; Sankaran, Shankar (Ascent Audio, 2022)
A new theory of balanced leadership in projects Leadership is not static. Instead, authority in projects shifts dynamically between project managers, individual team members, and sub-teams, depending on the situation. Leadership may be exercised through a vertical, horizontal, shared, or distributed leadership approach. However, balanced leadership ensures the best suitable approach is used in any given situation. Based on an award-winning global program of research studies, Balanced Leadership is a thorough investigation of balanced leadership in projects. Ralf Müller, Nathalie Drouin, and Shankar Sankaran present a project-specific leadership approach as well as a theory of balanced leadership, and the situations in which different strategies are required. They also outline the five building blocks that enable balanced leadership: nomination of team members, identification of potential leaders, selection and empowerment of leaders, empowered leadership and its governance, and leadership transition. The book explains the coordination of these building blocks through the socio-cognitive space shared by project manager and team. Using real-life case studies and clear examples, this book offers a new way of considering and utilizing dynamic leadership in project settings.